Mengenbüro : Chronik - Jahresgaben 1998 - Ausstellung. (Aachen : NAK (Neuer Aachener Kunstverein) Aachen, 1998)
Ackermann, Franz ; Ando, Yukako ; Danke, Raphael ; Danke, Tobias ; Fleury, Sylvie ; Giustina, Cristina Della ; Gundlach, F.C. ; Locher, Thomas ; Meese, Jonathan ; Miller, John ; Möller, Regina ; Reinert, Jens ; Richter, Gerhard ; Roth, Dieter ; Wohnseifer, Johannes
biografie
Mengenbüro, NAK (Neuer Aachener Kunstverein) Aachen, 27/08 - 27/09/1998
boek